Prolonged stabilization of platinum-refractory ovarian cancer in a single patient undergoing long-term Mistletoe extract treatment: Case report. Issue 8 (February 2019) - Hwang, Woo Yeon; Kang, Mi Hyun; Lee, Seul Ki; Yeom, Ji Su; Jung, Min Hyung
Abstract: Rationale: Advanced ovarian malignancies are associated with poor overall survival; thus, patients often turn to alternative treatments, despite the controversy surrounding their use. Mistletoe extract has been commonly used as complementary medicine to treat patients with cancer for several decades, and has proven benefits in integrative oncology. Patient concerns: A 47-year-old woman with stage IVB ovarian cancer who underwent optimal surgical cytoreduction, but whose disease persisted after adjuvant platinum-based combination chemotherapy and 2nd-line chemotherapy. Diagnosis and interventions: The patient discontinued chemotherapy due to her septic condition and acute kidney injury accompanied by acute pyelonephritis, and opted for adjuvant treatment with mistletoe extract. Outcomes: The patient has achieved good health without progression of cancer or ascites over the 42 months since the 1st diagnosis and 24 months since the last relapse. Lessions: Our case suggests that mistletoe extract can produce favorable outcomes in patients with platinum-refractory ovarian cancer.